Can industrial agglomeration alleviate energy poverty? Evidence from China - Xiaomeng Zhao; Yichuan Xie; Qingzhe Jiang; Jun Zhao (Chinese Journal of Population, Resources and Environment)
This study determines whether industrial agglomeration can solve energy poverty (ENPO) by applying a provincial dataset (2002–2019) to assess the potential effect of industrial agglomeration on ENPO. Additionally, this study conducts an in-depth exploration of provincial heterogeneity and its influence mechanisms. The conclusions are as follows: ① Industrial agglomeration is negatively correlated with ENPO; by implication, enhancing industrial agglomeration is a driving force for reducing ENPO. ② The alleviating effect of industrial agglomeration on ENPO in the midwestern region is considerably higher than that in the eastern region, and the ENPO alleviation effect of the high agglomeration region is better than that in the low agglomeration region. ③ Foreign investment and energy efficiency have a mediating role, that is, they are valid transmission pathways for industrial agglomeration to solve the ENPO issue. Relevant policy suggestions for reducing ENPO by accelerating industrial agglomeration are proposed by drawing on the above three conclusions.